2018
DOI: 10.1101/262139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AnEscherichia colinitrogen starvation response is important for mutualistic coexistence withRhodopseudomonas palustris

Abstract: Microbial mutualistic cross-feeding interactions are ubiquitous and can drive important community functions. Engaging in cross-feeding undoubtedly affects the physiology and metabolism of individual species involved. However, the nature in which an individual’s physiology is influenced by cross-feeding and the importance of those physiological changes for the mutualism have received little attention. We previously developed a genetically tractable coculture to study bacterial mutualisms. The coculture consists… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Low formate yields could also be explained by decreased formate production by E. coli in favor of other fermentation products that R. palustris can readily consume. We previously observed low formate yields in slow-growing, nitrogen-limited NifA*-based cocultures (19, 20), suggesting that formate production by E. coli varies in response to growth rate. We have also not ruled out the possibility that R. palustris can consume some formate under certain conditions.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Low formate yields could also be explained by decreased formate production by E. coli in favor of other fermentation products that R. palustris can readily consume. We previously observed low formate yields in slow-growing, nitrogen-limited NifA*-based cocultures (19, 20), suggesting that formate production by E. coli varies in response to growth rate. We have also not ruled out the possibility that R. palustris can consume some formate under certain conditions.…”
Section: Resultsmentioning
confidence: 97%
“…NtrC and the histidine kinase NtrB form a two-component system that senses and coordinates the nitrogen starvation response in E. coli (30, 31). Our lab previously found that the E. coli NtrBC-regulon is highly expressed in coculture with R. palustris NifA* (20). Thus E. coli NtrBC might be even more important in coculture with WT R. palustris wherein E. coli nitrogen starvation is expected to be intensified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our lab used transcriptome sequencing (RNA-Seq) and proteomics to interrogate how cross-feeding impacts the physiology of each species (37). This study revealed that the E. coli NtrC-mediated nitrogen starvation response (NSR) is crucial for fitness in coculture (37). However, RNA-Seq does not necessarily identify genes that confer fitness under the tested conditions.…”
Section: Introductionmentioning
confidence: 99%